Georgia in the Turkish School History Textbooks - Bardadze, Sofio (Politics / პოლიტიკა; 2019: მეოთხე ნომერი, 2020)
The work deals is the history of Turkish schools. It was important for us to analyze Georgia the eyes of the neighbour country’s school books. In the research for the visible we dedicated a other chapter to see the place of Turkey in the Georgia’s school books to the in order to see the difference between the perception of the history of the two countries. The present work is based about the books currently accredited in Turkey and Georgia. Also, writing materials and verbal concepts. The news in the research is the fact that the history of Turkish school has never been seen and has not given priority to how the Turkish state is informed about neighbor country his citizens in which its ethnic Georgians are also very much. The subject of research is the perception of the history of ethnically Georgian population assimilated in Turkey, centuries ago and almost entirely Turkish side, based on the history books taught in school.